(untitled) (Global Journal of Management and Business Research, 2018)
Although Information and Communication Technology (ICT) provides enormous opportunities such as storing, processing, retrieving, disseminating and sharing of information, its use within SMEs in developing countries is still plagued with many problems that hinder effective and efficient management towards the achievement of competitive advantage in the global market. The idea that there is a strong relationship between the process of globalization, information and communications technology and the development of entrepreneurship has long been established in the literature and research. In this paper, the study put the discourse of ICT and the process of globalization in the context of entrepreneurial development in Sub-Saharan Africa. Through a theoretical analysis of the extant literature, the study examined the forces shaping the global economy, especially the ubiquitous impact of ICT in terms of enterprise competitiveness. Arguments proferred points to the future of SMEs and entrepreneurial firms in Sub-Saharan Africa are anchored on the development of a viable ICT infrastructure. Secondly study examines the importance of ICT in enterprise development and its role in the development and growth of SMEs. Third, the paper examines the obstacles and challenges facing the adoption of ICT among SMEs and entrepreneurial firms in Sub-Saharan Africa. Finally, it suggests some strategies at the disposal of governments and owner/managers of entrepreneurial firms and SMEs to enhance the competitiveness of their national economies and of individual firms respectively in the global economy.